Factors Associated with the Incidence of Sibling Rivalry in Children Aged 3-10 Years in the Agricultural Area, Jember - Nabilah Artha D.Z.; Ira Rahmawati; Merina, Nuning Dwi; Lantin Sulistyorini (KHD-Production, 2024)
Sibling rivalry is a competitive feeling that occurs between siblings. Children will show their sibling rivalry by behaving temperamentally, such as crying loudly for no reason, extreme behavior to bind their parents' attention, or even behaving violently and even committing violence against their younger siblings. This jealousy does not always arise in the first child who will have a younger sibling, where some research results mention that second and third children can also feel jealous of their younger siblings. Factors associated with the incidence of sibling rivalry are the level of knowledge, parental attitudes, age gap and gender of the child. Factors associated with the incidence of sibling rivalry are the level of knowledge, parental attitudes, age distance and gender of the child. Factors associated with the incidence of sibling rivalry are the level of knowledge, parental attitudes, age distance and gender of the child. The purpose of this study was to determine the factors associated with the incidence of sibling rivalry in children aged 3-10 years in the agricultural area. This study used a descriptive analytic research design with a cross-sectional approach with a sample of 108 respondents. The results showed that the level of knowledge and attitudes of parents were related to the incidence of sibling rivalry with the results of the level of knowledge p-value 0.02 and parental attitudes with p-value 0,03 which means a significant relationship between the two variables. Advice for parents to increase cooperation in overcoming sibling rivalry and find ways so that it does not have a negative impact on child development.